Shear Force at Failure and Stiffness of All-Inside Meniscal Repair Devices - Kesto, William K.; Esquivel, Amanda O.; Markel, David C. (The Journal of Knee Surgery, 2013)
The purpose of this study was to determine the failure load and stiffness of various meniscal repair devices. A total of 61 fresh-frozen porcine menisci (medial and lateral) were used for the study. A 30-mm vertical, full-thickness tear was created and repaired using one of three all-inside fixation devices and one inside–out repair in the vertical mattress pattern. We used the MaxBraid (Biomet, Warsaw, IN) inside–out suture as a control. The other devices tested were the Meniscal Cinch (Arthrex, Naples, FL), Ultra FasT-Fix (Smith & Nephew, Andover, MA), and the MaxFire MarXmen (Biomet, Warsaw, IN). In addition, two devices, MaxFire MarXmen and Ultra FasT-Fix, were tested using a horizontal mattress configuration. Using the vertical mattress pattern, the Meniscal Cinch had the highest average load to failure. The Meniscal Cinch was significantly less stiff than the other three devices (p < 0.04). For the MarXmen and Ultra FasT-Fix, no differences were noted for load to failure between horizontal and vertical mattress patterns. The mode of failure was significantly different when comparing the two different surgical techniques for the MaxFire MarXmen (p = 0.005). The MaxFire MarXmen device produced a significantly stiffer (p < 0.001) construct when following the manufacturer's instructions (5.8 N/mm) than with the technique used for the other all-inside devices (2.5 N/mm) The Meniscal Cinch had the highest load-to-failure value but the lowest stiffness of the group in the vertical mattress configuration. There was little difference in biomechanical properties between vertical and horizontal repair. Importantly, there was a significant difference in stiffness and failure mode for the MaxFire MarXmen when the manufacturer guidelines were not specifically followed.
Keywords: meniscal repair; meniscus biomechanics; all-inside fixation devices; knee